Лев и собачка: рассказы / Л. Н. Толстой - Толстой Лев Николаевич (Внеклассное чтение, 2007)
Экземпляры: М/а ДБ (20081121) / Инвентарный номер: 92798 / Цена: 28.27 / Авт.знак: Т 53 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1